Faktor Determinan Kasus TB Paru di Wilayah Kerja Puskesmas Pamarican Kabupaten Ciamis - Annashr, Nissa Noor; Laksmini, Puji (Jurnal Kesehatan Komunitas, 2023)
In 2021, the Pamarican Health Center had the second-highest cases of pulmonary TB in the Ciamis Regency. This study aimed to analyze the determinant factors of the incidence of pulmonary TB in the working area of the Pamarican Health Center. This study used a case-control design. The case population was all patients at the Pamarican Health Center from 2021 to July 2022 who had confirmed smear pulmonary TB (+) and residing in the working area of the Pamarican Health Center, namely 34 people. Meanwhile, the control group consisted of all patients at the Pamarican Health Center from 2021 to July 2022 who tested negative for pulmonary TB, namely 416 people. Selection of case samples using total sampling, while control samples using purposive sampling. The comparison of cases and controls is 1: 2 so the sample size of cases and controls was 34: 68. Data was collected through interviews using a questionnaire, observation using observation sheets, and direct measurements using a roll meter. Data analysis used univariate analysis, the bivariate analysis used chi-square and Fisher's exact tests, and multivariate analysis used multiple logistic regression. The results of the bivariate analysis showed that 2 variables were proven to have a significant relationship with the incidence of pulmonary TB, namely marital status (p = 0.038; OR = 2.774, 95% CI: 1.038-7.414), comorbid diseases (p = 0.006; OR = 6.667; 95% CI: 1.640 – 27.107). Based on the results of multivariate analysis, it was known that there was one variable that was most related to the incidence of pulmonary TB, namely the comorbid disease variable, with an OR of 5.302 (95% CI: 1.215 – 23.146). Based on the research results, it was suggested to the American Health Center to continue to monitor and control comorbid diseases, namely DM, which is a risk factor for TB transmission